Religion Faith and Thought the Tribe of Meghalaya in North East India - Dr. Gargi Phukan (International Journal of Advanced Science and Technology, 2020)
While discussing the tribe and caste situation we cannot avoid reference to the tribe and caste of North Eastern India. This region is a veritable tribal museum of more than 200 tribes with variations culturally, linguistically and even socio-politically, comprising eight states almost all of whom constitute greater Assam under the common ethnicity called Indo-Mongoloids. The tribal populations of the region speak different dialects having distinct socio-cultural relations distinguishable from one another. Although generally the tribes belong to Mongoloid stock, yet Australoid element has also become discernable. North East India is a confluence of people, popularly described as tribes, living in different stages of under-development and, in most cases, without a written history of their own. Meghalaya is the homeland of three tribes- The Garos, the Khasis and the Jainties. This is the only state where the main inhabitants follow matrilineal system of inheritance. Through it inheritance to property and succession to tribe office, both run through the female line, passing from the mother to the youngest daughter. This is all the more striking because the three groups belong to different ethnic backgrounds. Like all tribal societies the Garos, the Khasis and the Jainties have certain social institution to form, guide and control the cohesive structure of family kinship and social relations among the clan within their respective traditional jurisdictions.